Translational bioethics: Reflections on what it can be and how it should work - Bærøe, Kristine (Bioethics, 2024)
Translational ethics (TE) has been developed into a specific approach, which revolves around the argument that strategies for bridging the theory‐practice gap in bioethics must themselves be justified on ethical terms. This version of TE incorporates normative, empirical and foundational ethics research and continues to develop through application and in the face of new ethical challenges. Here, I explore the idea that the academic field of bioethics has not yet sufficiently analysed its own philosophical foundation for how it can, and should, be practically relevant; neither has it comprehensively discussed the limitations on what impacts bioethicists should pursue. As a result, there has not been adequate training on how to suitably and appropriately impact real‐world practices. Moreover, bioethical perspectives are often competing with other strong interests, for example, economic and political, which may weaken their impact on policy‐making. The TE approach I propose can not only facilitate practical impacts of academic bioethics by being better informed by real‐world ethical issues but it also supports targeted and ethical justifications of the actual impact of academic work in real‐world contexts. In this paper, I clarify the premises for this TE approach, identify further challenges and sketch out potential solutions for the implementation of this methodological framework.